LOS ESTADOS INMADUROS DE 7 ESPECIES NEOTROPICALES DEL GENERO DASYBASIS MACQUART (TABANIDAE, DIPTERA, INSECTA) - Coscaron, Sixto (Acta Entomológica Chilena, 2022)
Larvae and pupae of Dasybasis andícola (Philippi), D. canipilis Kroeber, D. opaca (Bréthes), D. testaceomaculata (Macquart), and pupa of D. chilensis (Macquart) are described; larva and pupa of D. fairchildi Coscaron 8c Philip and D. nigra (Enderlein) are redescribed. A genus diagnosis based on immatures, keys and illustrations are included.